THE STALEMATE OF THE SOCIAL THEORY OF CLASSICAL MARXISM BY USING SUSTAINABLE SUPPLY CHAIN OPERATIONS - Vorontsova, V.L.; Salimgareev, M.V.; Salimgareev, D.V.; Ramazanov, A.V. (International Journal of Supply Chain Management, 2019)
Abstract- The article discusses a number of key theoretical principles of classical Marxism, such as supply chain management, whichare important for understanding the essence of this teaching. Some essential methodological guidelines of the materialist theory of Marxism are analyzed. The most important components of anthropology are considered. An attempt is made to criticize the materialist understanding of historical development. The authors are convinced that Marxism, trying to cover the entire history in a holistic manner, is not explaining particular events through universal categories. For a holistic explanation of this universality, it is necessary to subject the entire historical process to a detailed manifestation of phenomenal reality by large-scale deconstruction. In this movement, the entire given reality of the material world must be disassembled into structural components and only then, from the emerging knowledge of all total integrity, can different aspects of similarities and differences be constructed, any objective specificity from which stable regular relationships and relationships are found. However, the historical process unfolding itself is manifested by its most important fundamental quality, which consists in the fact that specific people, nations, nations have a unique spiritual manifestation. In the space of the latter there are no strict conditions for total universality. From this, the description of the objectivity arising in the sphere of consciousness cannot be verified by known methods of the natural sciences. The authors conclude that any accurate knowledge of the spiritual sphere of human life is difficult to achieve, if at all, because consciousness is not an elementary particle, phenomenologically it is primarily a complex ontological reality, determined not by anyoneâ??s consciousness or by being, but by the sum of various factors.